The Impact of Teacher Training and Experience on Performance: Strengthening Educational Quality Through Professional Development - Prastyo Nugroho (Journal of Islamic Studies and Education, 2024)
Teacher performance plays a pivotal role in shaping the quality of education, as it directly influences student learning outcomes. Effective teachers demonstrate strong instructional skills, classroom management, and the ability to adapt to evolving educational needs. This study explores the impact of training and experience on teacher performance, emphasizing how professional development and hands-on practice contribute to enhanced teaching effectiveness. Through a literature review-based methodology, the study examines existing research on the correlation between training, experience, and teacher performance. Findings indicate that ongoing training equips teachers with modern pedagogical techniques and technological integration, while experience allows for improved adaptability, problem-solving, and classroom engagement. Additionally, the study highlights the role of school leadership in fostering a culture of continuous learning, ensuring that teachers receive the necessary support for professional growth. The results suggest that a structured approach to teacher development, combining training initiatives with practical experience, is essential for sustaining high teaching standards and improving student achievement. Future research should further investigate the optimal balance between training and experiential learning to maximize teacher effectiveness in diverse educational settings.